2012
DOI: 10.1002/aic.13793
|View full text |Cite
|
Sign up to set email alerts
|

Transport in deformable hygroscopic porous media during microwave puffing

Abstract: Microwave puffing is a process used to obtain low‐fat healthy foods by rapid heating of food products to develop high internal pressures in the material that cause significant structural changes. Two‐way coupling of complex multiphase transport and large deformations in the material, which is critical to simulate the puffing process accurately, was implemented. A porous media model that includes different phases, solid, liquid water, and gas, and incorporates pressure driven flow and evaporation was used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 58 publications
(67 reference statements)
0
20
0
Order By: Relevance
“…The popcorn kernel pericarp not only provides protection and containment to the endosperm, but also acts as a pressure vessel during heating, which gives popcorn its characteristic popping ability (PEREIRA et al, 2008). As heat is applied to popcorn, the pericarp limits kernel moisture loss and facilitates vapor pressure build-up and water superheating within the kernels (RAKESH et al, 2013). SWELEY et al (2013) suggested the use of pericarp thickness as an indicator of popping quality.…”
Section: Pericarp Thicknessmentioning
confidence: 99%
“…The popcorn kernel pericarp not only provides protection and containment to the endosperm, but also acts as a pressure vessel during heating, which gives popcorn its characteristic popping ability (PEREIRA et al, 2008). As heat is applied to popcorn, the pericarp limits kernel moisture loss and facilitates vapor pressure build-up and water superheating within the kernels (RAKESH et al, 2013). SWELEY et al (2013) suggested the use of pericarp thickness as an indicator of popping quality.…”
Section: Pericarp Thicknessmentioning
confidence: 99%
“…The limited reported data are for raw potato (Ni and Datta ; Datta ), meat (Datta ), bread (Goedeken and Tong ), and apple (Feng and others ). In porous media transport modeling, researchers have used a wide range of water and gas permeability values that can vary by more than 2 orders of magnitude from 10 −14 to 10 −17 m 2 for different food products (Halder and others 2007a; Dhall and others ; Rakesh and Datta ). In this study, we used 10 −15 and 10 −14 m 2 for intrinsic permeability of water and gas, respectively, which are in range of reported values in the literature.…”
Section: Model Developmentmentioning
confidence: 99%
“…The diffusion coefficient is a strong function of moisture content, temperature, and structure (void fraction, prestructure, and distribution) of the material (Gulati and Datta ). Different diffusion coefficients of water and gas have been used in modeling of different process of different food products, varying from 10 −7 to 10 −8 m 2 /s for liquid water (Rakesh and Datta , ; Dhall and others ; Warning and others ), and from 10 −5 to 10 −6 m 2 /s for water gas (Halder and others 2007a; Rakesh and Datta , ; Dhall and others ). In this study we used the value of 1 × 10 −7 .exp (−2.8 + 2M) for liquid water and 2.6 × 10 −5 m 2 /s for gas, which were reasonable estimations.…”
Section: Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations